Odpowiedzi

2009-04-20T19:15:30+02:00
A) = 2x - 3y - x -y = x - 4y
B)= -a -2 -a -b +2 = -2a -b
c) = 3x + 3y - 15
d) x + 2y - 3x - 12 + 2y +1 = 2x + 4y -11
2009-04-20T19:17:07+02:00
A) (2X - 3 y) - ( x + y) = 2x - 3y - x - y = x - 4y
b) -(a + 2) - ( a + b - 2) = -a -2 - a - b + 2 = -2a - b
c) (-3) ( - x - y + 5) = -3 - x - y + 5 = 2 - x - y
d) ( x + 2y) - 3 ( x + 4 ) + ( 2y + 1) = x + 2y - 3x - 7 + 2y + 1 = - 2 x + 4y - 6

Jak chcesz moge wytlumaczyc za 1 pkt. ^^
2009-04-20T19:18:05+02:00
A)(2x-3y)-(x+y)=2x-3y-x-y=x-4y
b)-(a + 2) - ( a + b - 2) = -a-2-a-b+2=-2a-b
c) (-3) ( - x - y + 5) =3x+3y-15
d) ( x + 2y) - 3 ( x + 4 ) + ( 2y + 1) =x+2y-3x-12+2y+1=2x+4y-11
2009-04-20T19:20:22+02:00
A) 2x-3y-x-y= x-4y
b) -a-2-a-b+2= -2a -b
c) -3(-x-y+5)= 3x+3y-15
d) x+2y-3x-12+2y+1= -2x+4y-11